Analisis Penyerapan Tenaga Kerja Kabupaten/Kota di Provinsi Kalimantan Selatan Tahun 2015 2019 - Sinta Claudia Fitaloka; Muhammad Rusmin Nuryadin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The research aims to verify and analyze the effect of GRDP, PMA, PMDN, capital expenditures, and minimum wages on labor absorption. The data are descriptive with secondary data. The analysis is panel data regression analysis, a combination of data for 2015 2019 and cross-section data for 13 districts/cities in South Kalimantan Province, which were processed using the REVIEWS 11 application.The results show that (1) GRDP, PMA, PMDN, capital expenditure, and minimum wages that affect the absorption of labor simultaneously; (2) The minimum wage have a significant positive, GRDP have an insignificant positive, PMA, PMDN, and capital expenditures have an insignificant negative effect on the absorption of labor district/cities in South Kalimantan Province in 2015 2019